The Impact of The Baznas Microfinance Village Program on Improving The Economic Welfare and Religiosity of Female Heads of Households - Muhammad Fathan Izzuddin; Cupian Cupian; Yudi Ahmad Faisal (UNIVED Press, 2026)
This study analyzes the impact of the BAZNAS Microfinance Desa (BMD) program on the economic welfare and religiosity of Female Heads of Households (PEKKA) in West Java. Using a mixed-method approach with SEM-PLS analysis and the CIBEST model involving 151 respondents, this study examines the influence of business capital, mentoring, and training. The SEM-PLS results indicate that business capital does not have a significant partial effect on economic welfare, whereas mentoring and training have a significant positive impact, with mentoring being the most dominant variable. Furthermore, the CIBEST analysis confirms the program's success through a drastic reduction in absolute poverty (material and spiritual) from 61 to 6 individuals, alongside a significant increase in the number of beneficiaries in the prosperous quadrant. The study concludes that financial assistance must be bundled with intensive mentoring to ensure sustainable economic independence and spiritual strengthening for PEKKA.